Pengembangan Media Quiz Card Treasure Berbasis Kearifan Lokal untuk Penguatan Kecerdasan Spasial Siswa di Sekolah Dasar - Angga Setiawan; Intan Susetyo Kusumo Wardhani; Wawan Prasetyo; Diyanti Jati Pratiwi; Lataniya Fie Dzikry (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the low spatial intelligence of elementary school students in visualizing abstract spatial concepts within Natural and Social Sciences (IPAS) learning. The objective of this research is to develop the Quiz Card Treasure medium based on Trenggalek local wisdom that is proven valid, practical, and effective in strengthening students' spatial abilities. The method employed is Research and Development (R&D) utilizing the ADDIE development model, which comprises the Analyze, Design, Development, Implementation, and Evaluation stages. The research subjects involved 75 fourth-grade students from three elementary schools in Trenggalek Regency. Data collection techniques included expert validation sheets, response questionnaires, and performance tests. The results indicate that the developed medium met the "very valid" criteria, with feasibility percentages of 90% for material, 92% for media, and 90% for instructional design. The practicality test received a very positive response, with 92% from teachers and 93% from students. The effectiveness test demonstrated a significant improvement in learning outcomes, achieving an average N-Gain score of 0.65, classified in the medium category. It is concluded that integrating treasure hunt game mechanisms with local wisdom content effectively stimulates students' visualization and directional orientation abilities, making it a suitable innovative learning solution for elementary schools.